Burnout and Coping Strategies in Male Staff from National Police in Valparaíso, Chile. - Daniel Briones Mella; Ana P Kinkead Boutin (Tehran University of Medical Sciences, 2013)
This cross-sectional study aimed to examine the relationship between several dimensions of the burnout syndrome with certain stress-coping strategies, seniority level and marital status in male staff from National Police in Vaparaíso, Chile.The sample collected in 2010 was composed of 338 male officers coming from various special units of a National Police in Valparaíso. Burnout and Coping Strategies were assessed and classified according Maslach Burnout Inventory (MBI) and COPE Inventory, respectively. Data was analyzed using Pearson product-moment correlation, t-test for independent measures and Multiple Linear Regression to generate a predictive model.The prevalence of the burnout syndrome disaggregated by grouping criteria, the dimensions concentrated in middle levels for emotional exhaustion with a 52.1%, a 51.8% for depersonalization and finally, personal achievement with a 48.8%. Only 28% of participants showed more exacerbated dimensions of the burnout syndrome. There was a weak and direct yet statistically significant relationship between personal achievement and active coping. Mental disconnection had a weak direct relationship between both coping strategies and emotional exhaustion also existed. Certain correlations between burnout dimensions and coping strategies focused on emotion as predictor variables over the criterion variable corresponding to emotional exhaustion were mental disconnection in first place, secondly, focusing on emotions, and emotional social support.Burnout dimensions scored medium values ​​focusing mainly on emotional exhaustion and reduced personal accomplishment. Coping strategies are used in parallel and in general are not mutually exclusive. Finally, there were not any relationship between variables seniority level and marital status.